Symmetry and fundamental physics : tom kibble at 80. - JEROME, GAUNTLETT (WSPC, 2013)
Tom Kibble is an inspirational theoretical physicist who has made profound contributions to our understanding of the physical world. To celebrate his 80th birthday a one-day symposium was held on March 13, 2013 at the Blackett Laboratory, Imperial College, London. This important volume is a compilation of papers based on the presentations that were given at the symposium. The symposium profiled various aspects of Tom's long scientific career. The tenor of the meeting was set in the first talk given by Neil Turok, director of the Perimeter Institute for Theoretical Physics, who described Tom as.